2017
DOI: 10.1111/aas.12864
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ultrasound‐guided interscalene and supraclavicular blocks for post‐operative analgesia after shoulder surgery

Abstract: This study showed no statistically significant difference in the duration of post-operative analgesia between the supraclavicular and interscalene blocks. However, the supraclavicular block was associated with a lower incidence of diaphragmatic paresis compared with that of the interscalene block after shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 23 publications
(24 reference statements)
3
47
2
2
Order By: Relevance
“…In that study, postoperative pain scores were only assessed at 2 time points (PACU and 24 hours) and reported as nondifferent between groups, similar to our study's finding. Likewise, the time to first analgesic requirement was also similar for each group in both studies …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In that study, postoperative pain scores were only assessed at 2 time points (PACU and 24 hours) and reported as nondifferent between groups, similar to our study's finding. Likewise, the time to first analgesic requirement was also similar for each group in both studies …”
Section: Discussionsupporting
confidence: 87%
“…22 However, recent studies have shown that the reduced volume and concentration of local anesthetic resulted in equivalent analgesia and increased patient satisfaction when compared to a traditional dose. 23,24 In another study, Kim et al 25 performed SCBB or ISBB with 20 mL 0.375% ropivacaine under US guidance as additional to general anesthesia in shoulder surgery and reported no statistically significant difference between groups regarding the duration of postoperative analgesia. In that study, 25 postoperative pain scores were only assessed at 2 time points (PACU and 24 hours) and reported as nondifferent between groups, similar to our study's finding.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, supraclavicular brachial plexus block (SCBPB) is a cost-effective anesthetic technique that is associated with low medical costs and a short length of hospital stay 1. Although SCBPB first became a popular approach for surgery distal to the shoulder, it has recently been used to provide analgesia for shoulder surgery 2. However, SCBPB is associated with ipsilateral hemidiaphragmatic paralysis at an estimated incidence of 36%–67%,3which has been attributed to the proximity of the phrenic nerve to the brachial plexus in the neck and the location and direction of diffusion of the locally applied anesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In a study performed after this review Kim et al compared the analgesic efficacy and side effects of interscalene and supraclavicular blocks for shoulder surgery using 20 ml of 0.375% ropivaciane and found no difference in postoperative analgesia duration, pain scores; and supplemental analgesia. [10] Ryu et al, [11] compared the anesthetic properties of these two blocks using 12.5 ml 1% mepivacaine, and 12.5 ml of 7.5% ropivacaine for similar shoulder surgery procedures and concluded that ultrasound guided supraclavicular blocks can be performed as an alternative to ultrasound guided interscalene blocks in patients undergoing arthroscopic shoulder surgery. Although focused more on the incidence of phrenic palsy in the PHRENICUS trial Wiesmann et al, [12] found that the postoperative analgesic quality and additional analgesic requirements of continuous supraclavicular blockade using patient-controlled ropivacaine was similar to interscalene group.…”
Section: Discussionmentioning
confidence: 99%